Local adaptation and genetic divergence in the dominant grass Andropogon gerardii across the Great Plains’ rainfall gradient - Galliart, Matthew (Kansas State University, 2023)
Many prior studies have uncovered evidence for local adaptation using reciprocal transplant experiments. However, these studies are rarely conducted for a long enough time to observe succession and competitive dynamics in a community context, limiting inferences for long-lived species. Furthermore, most studies lack comprehensive investigation with only few responses or measurements included, and lack integrative studies combining both ecology and genomics. Here, we report on a long-term experiment focused on Andropogon gerardii, the dominant grass of the North American Great Plains tallgrass ecosystem. Our approach used a reciprocal garden platform in which four reciprocal garden sites were planted with three regional ecotypes of Andropogon gerardii, using dry, mesic, and wet ecotypes originating from western KS to Illinois that span 500–1,200 mm rainfall/year. We focus on this foundation grass that comprises 80% of tallgrass prairie biomass, is a major forage grass for cattle, and is widely used in restoration. First, we aimed to assess genetically based local adaptation of A. gerardii ecotypes in realistic competitive settings. We addressed the following questions: 1) Do ecotypes display local adaptation to regional climate when planted in realistic ecological communities? 2) Does adaptive genetic variation underlie divergent phenotypes? 3) Do we see evidence of local adaptation if the plants are exposed to competition among ecotypes of A. gerardii in mixed ecotype plots? 4) Is local adaptation related to climate gradients? We demonstrate local adaptation and differentiation of ecotypes in wet and dry environments. Surprisingly, the apparent generalist mesic ecotype performed comparably under all rainfall conditions. Ecotype performance was underpinned by differences in neutral diversity and candidate genes corroborating strong differences among ecotypes. Ecotype differentiation was related to climate, primarily rainfall. Second, we used the reciprocal gardens in plants growing singly without competition to detect genetic and environmental plasticity effects on phenotypic variation and combined with genetic analyses. The goal was to evaluate the extent to which A. gerardii ecotypes differ across spatially varying climatic regions, thus potentially signaling local specialization, i.e., genetic differentiation and adaptation of ecotypes to precipitation. Here we addressed the following questions: 1) Are A. gerardii ecotypes locally adapted to environment across the precipitation gradient? 2) What is the relative role of genetic constraints and plasticity in controlling phenotypic differences? 3) How will different ecotypes of A. gerardii respond under different climatic conditions, especially precipitation, when planted in home environment and reciprocally transplanted into foreign environments? 4) What are the underlying genetic bases for these traits? 5) How are genotypes and phenotypes structured by climate? Surprisingly, we did not detect consistent local adaptation. Rather, we detected co-gradient variation primarily for most vegetative responses. All ecotypes were stunted in western KS. Eastward, the wet ecotype was increasingly robust relative to other ecotypes. In contrast, fitness showed evidence for local adaptation in wet and dry ecotypes with wet and mesic ecotypes producing little seed in western KS. Earlier flowering time in the dry ecotype suggests adaptation to end of season drought. The wet ecotype was robust, tall with high biomass, and wide leaves putatively adapted for the highly competitive, light-limited Eastern Great Plains. We detected genetic differentiation and outlier genes associated with primarily precipitation. We identified candidate gene GA1 for which allele frequency associated with plant height. Sourcing of climate adapted ecotypes should be considered for restoration. Finally, we aimed to determine to what extent this ecologically-important prairie grass, big bluestem, responds to environmental change, both ecologically and transcriptionally through expression of genes. Here we aimed to answer: 1) Do bluestem ecotypes growing across a longitudinal precipitation gradient transcribe a different suite of genes or show differential expression levels of the same genes in response to environment? 2) Is the local ecotype of big bluestem more transcriptionally responsive in its home environment? and 3) How does an ecologically important grass respond ecologically and at the level of its transcriptome to a drier or wetter environment at the margin of its range? Without long-term studies, wrong conclusions would have been reached based on insufficient data. Ultimately, restoring and conserving prairies with climate-matched ecotypes is critical to future ecology, conservation, and sustainability of these vital grasslands under climate change.
Keywords: Ecological genomics; Local adaptation; Adaptive variation; Big bluestem